Mobilization of soil-borne arsenic by three common organic acids: Dosage and time effects. (March 2016) - Onireti, Olaronke O.; Lin, Chuxia
Abstract: A batch experiment was conducted to investigate the mobilization of soil-borne arsenic by three common low-molecular-weight organic acids with a focus on dosage and time effects. The results show that oxalic acid behaved differently from citric acid and malic acid in terms of mobilizing As that was bound to iron compounds. At an equivalent molar concentration, reactions between oxalic acid and soil-borne Fe were kinetically more favourable, as compared to those between either citric acid or malic acid and the soil-borne Fe. It was found that reductive dissolution of soil-borne Fe played a more important role in liberating As, as compared to non-reductive reactions. Prior to the 7th day of the experiment, As mobility increased with increasing dose of oxalic acid while there was no significant difference (P > 0.05) in mobilized As among the treatments with different doses of citric acid or malic acid. The dosage effect on soil-borne As mobilization in the citric acid and malic acid treatments became clear only after the 7th day of the experiment. Soluble Ca present in the soils could cause re-immobilization of As by competing with solution-borne Fe for available organic ligands to form practically insoluble organic compounds of calcium (i.e. calcium oxalate). This resulted in transformation of highly soluble organic complexes of iron (i.e. iron oxalate complexes) into slightly soluble organic compounds of iron (i.e. iron oxalate) or free ferric ion, which then reacted with the solution-borne arsenate ions to form practically insoluble iron arsenates in the latter part of the experiment. Highlights: Investigation into mobilization of soil-borne arsenic by low-molecular-weight organic acids. Oxalic acid was more dose- and time-efficient than citric and malic acids for As mobilization. Reductive Fe dissolution was more important than non-reductive reactions in liberating As. Soluble Ca could cause As re-immobilization by competing with Fe for organic ligands. Implications for understanding As behaviour in rhizospheric soil environments.